Proceedings of the Conference on Wireless Health 2012
DOI: 10.1145/2448096.2448105
|View full text |Cite
|
Sign up to set email alerts
|

Wanda

Abstract: Recent advances in wireless sensors, mobile technologies, and cloud computing have made continuous remote monitoring of patients possible. In this paper, we introduce the design and implementation of WANDA, an end-to-end remote health monitoring and analytics system designed for heart failure patients. The system consists of a smartphone-based data collection gateway, an Internet-scale data storage and search system, and a backend analytics engine for diagnostic and prognostic purposes. The system supports the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…In recent years, telemonitoring has shown promise for various health management programs, such as reducing readmission rates for heart failure patients [29,30] and for diabetes management [31,32]. However, most telemonitoring systems have been designed with providers as the primary users and designers have overlooked patient roles in providing context and interpreting symptom data [33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, telemonitoring has shown promise for various health management programs, such as reducing readmission rates for heart failure patients [29,30] and for diabetes management [31,32]. However, most telemonitoring systems have been designed with providers as the primary users and designers have overlooked patient roles in providing context and interpreting symptom data [33].…”
Section: Introductionmentioning
confidence: 99%
“…Mamykina et al conducted a series of studies showing the value of using tracked data in diabetes care between patients and their care team and how patients used the data and tools to make sense of their illness and care management trajectories [38,39]. Many of these systems have demonstrated that features supporting collaboration can successfully provide necessary contextual information for diagnosis [55], facilitate communication [2,47,52], engage patients in the shared decision-making process [3], and support long-term care management [31,50,56].…”
mentioning
confidence: 99%
“…Most planned outlines for RHW Sin uence a three-tier style: A WBAN containing of portable sensors because knowledge acquisition element, and service layer., for example, suggests a scheme that converts portable sensors to live varied physical parameters like vital sign and vital sign [11]. Sensors convey the collected data to entranceway server over a Bluetooth connotation [12]. The entranceway server goes information into associate Surveillance and activity folder and provisions it on distant server for advanced repossession by clinicians over web.…”
Section: Healthcare Monitoring System Using Wsn With Iotmentioning
confidence: 99%